Democracia e Constituição: a evolução das dimensões da democracia nas Constituições brasileiras - Saiter, Jaqueline Coutinho (2005)
Treats of the evolution of the dimensions of the democracy in the Brazilian Constitutions, in other words, of the analysis of the several meanings that the democracy presented in the constitutional history of Brazil. Leaves, initially, of the understanding that the democracy constitutes a cultural production, due to the group of factors social, political, juridical, economical and cultural that form a society. Approaches, soon afterwards, the three dimensions that the democracy assumes, which are the politics, the juridical and beginning. Analyzes, firstly, the political dimension, that it qualifies the democracy as modality of political regime. In a second moment, treats of the juridical dimension, that understands the democracy as fundamental right. Finally, brings the dimension os the beginning, marked by the qualification of the democracy as constitutional beginning. That dimension, in matter, is subdivided in two beginnings: the democratic representative and the democratic of the participation. Once tacked the theoretical outline, the research starts to approach the application of the three dimensions of the democracy in the Brazilian Constitutions. Begins with the study of the Constitutions of 1824, of 1891, of 1934 and of 1937, in which the democracy is allocated as political regime; soon afterwards, treats of the Constitutions of 1946 and of 1967 and of the Constitutional Amendment of 1969, that adopt the democracy as fundamental right; in a third moment, it approaches the Constitution of 1988, in the which the democracy can be considered as constitutional beginning. Analyzes, still, the content of the democracy in the respective constitutions, always considering the decisive political facts of each time. Conclude, at the end, of way circunstanciada, detaching the evolutionary construction of the democracy in the Brazilian constitutional history.